PENGARUH PENGGUNAAN MEDIA BUKU CERITA TERHADAP KEMAMPUAN MEMBACA SISWA PADA PEMBELAJARAN BAHASA INDONESIA KELAS IV SD NEGERI 120 BAROKO KABUPATEN ENREKANG - Fika Adha, Idfa Luth; Paida, Andi; Akbar, Amal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of storybook media on the reading comprehension skills of fourth-grade students in Indonesian language learning at SD Negeri 120 Baroko, Enrekang Regency. This study used a quantitative approach using a One Group Pretest-Posttest Experiment design. The sampling technique used was total sampling, with 13 students as the population in the fourth grade. The instruments used in this study were observation sheets and test sheets (pretest and posttest). Data analysis techniques used were descriptive statistical analysis and inferential statistical analysis, as well as hypothesis testing (t-test). The results showed that the reading comprehension skills of fourth-grade students at SD Negeri 120 Baroko, Enrekang Regency, before the use of storybook media were in the low category, with an average pretest score of 46.46. However, after the use of storybook media, there was a significant increase, with an average posttest score of 87.07. The results of the t-test analysis show that the significant value of 0.001 is smaller than the significant level of 0.05 (0.001 ≤ 0.05), so H0 is rejected and H1 is accepted. The hypothesis testing can be concluded that the use of storybook media has a significant effect on students' reading ability in Indonesian language learning for grade IV of SD Negeri 120 Baroko, Enrekang Regency.